Evaluation Study: Does The Sharia Supervisory Board Have A Direct Effect on Profitability? - Mukhibad, Hasan; Anisykurlillah, Indah (IAIN Salatiga, 2020)
Previous studies have indicated a complex relationship between the total Sharia Supervisory Board (SSB) members and profitability. Therefore, this study suspects that financing products and bank fundraising mediate the relationship between SSB and ROA. SSB can provide consultation and supervision on the implementation of bank products. Data were obtained from 12 Islamic commercial banks in Indonesia with a 10-year observation period (2009-2018). Data were analyzed using fixed and random effect models and path analysis. The results showed that the total SSB members and their expertise did not have a direct effect on ROA. However, it has an effect on financing and none on Investment Account Holders (IAH) funds. The results also showed that financing proved to be a mediating variable on the effect between the total and expertise of SSB members towards ROA. The IAH fund is the mediating variable on the effect between the total SSB members towards ROA, with no proven relationship. Therefore, it can be concluded that SSB has an indirect effect on ROA by strengthening the financing and bank fundraising quality. Consultation and supervision carried out by SSB on the implementation of IAH financing and fundraising, has proved to have an impact on improving bank profitability